Double vision - Barker, Pat 1943- (Farrar, Straus and Giroux, 2003)
Profoundly affected by the events of September 11th and its aftermath, two British journalists return to England to face different fates, in a study of the effects of violence on those who come in contact with it.
Keywords: Divorced men -- Fiction; Journalists -- Fiction; Psychological fiction.; Violence -- Fiction; Widows -- Fiction; England -- Fiction; Psychological fiction